Produksi protein sel tunggal mikroalga (Chlorella vulgaris) menggunakan limbah ayam broiler dan aplikasinya dalam pakan : Production of microalgae single-cell protein (Chlorella vulgaris) using broiler chicken waste and its application in feeds - Iba, Wa; Padang, Crasilia Yanti; Sari, Nilam; Ambardini, Sri; Suriana, Suriana (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Single-cell proteins from microalgae have the potential for use in broiler chicken feed formulations. One of the microalgae that has been widely developed today is Chlorella vulgaris. This study aimed to determine the concentration of C. vulgaris cultivated using organic media derived from broiler chicken waste and its protein content in feed. C. vulgaris was cultured using organic media from broiler chicken feces in seawater at 4 concentrations (10, 100, 1,000, and 10,000 ppm). The protein content of C. vulgaris and the feed was analyzed using the Kjeldahl method. The highest protein content was obtained from C. vulgaris in chicken fecal media at 10 ppm, which was 23.53%. The biomass of C. vulgaris cultured in 10 ppm chicken feces medium was added to the formulation of broiler chicken feed at different concentrations (0, 2.5, 5, 7.5, and 10 %) with three replicates. The highest protein content (34.65 %) was observed with the addition of 2.5% C. vulgaris biomass. The protein content that approached optimal levels for broiler chickens in the pre-starter and starter phases, which were 22.71% and 24.06%, respectively, was obtained with the addition of 5% and 7.5% C. vulgaris.